The Evaluation of Needs and Weaknesses of The Immunization Program in Kodingareng and Barranglompo Island, Makassar City, South Sulawesi, Indonesia - Hasanuddin, Asni; Jurnal Syarif; Ricvan Dana Nindrea (PT Inovasi Pratama Internasional, 2022)
Objectives: This study evaluates the needs and weaknesses of the immunization program in the Kodingareng Island and Barranglompo Islands, Makassar City, South Sulawesi, Indonesia. Materials & Methods: This research is qualitative research at the Center Health Service islands Kodingareng and Barranglompo Makassar City. Research informants were the head of the Sub-Health Service, immunization officers, immunization cadres Kodingareng Islands and Barranglompo Makassar City. The data analysis was done by triangulation.Results: The results showed that there was still a lack of immunization executors on the input component, vaccines were not available on the island because they were constrained by electricity intake to maintain the stability of the vaccine storage temperature. Funding support has not been able to support the operation of the immunization program. Apart from that, community empowerment is still not optimal. Infrastructure is constrained by the storage area for vaccines on the island which is not supported by adequate electricity intake. Vaccines cannot be stored in the area closest to the island because there are no storage facilities and also limited electricity intake. This causes officers after visiting the immunization site to immediately carry out vaccination activities.Conclusions: The needs and weaknesses in the immunization program in the Kodingareng and Barranglompo Island areas of Makassar City are the need for immunization implementing officers, the availability of vaccines on the island by strengthening funding support, and the availability of facilities through the provision of generators to support vaccine storage. Apart from that, the community is still lacking in terms of community empowerment.